Philosophy of Liberal Nationalism in the context of Refugee Immigration - Ahluwalia, Shaheena (Tattva Journal of Philosophy, 2022)
In recent times, the world has seen an explosion of episodes of forced migration. Whether another state has led the attack, such as Russia’s invasion of Ukraine or by its own state such as Myanmar, ousting the Rohingyas, this international political reality of forced exit can neither be denied nor ignored. Consequent to the international political reality, some states have tightened their borders as they hold nationalist concerns against immigration of such kind. Their concern stems from the philosophy of nationalism which claims the protection of borders and sovereignty in light of the influx of refugees and the burden on the state. This paper aims to elaborate on the interaction of political and legal philosophy related to Liberalism and Nationalism. I put forward the hypothesis that the current reality of international politics - the influx of victims of forced migration such as refugees should be rethought with the application of the philosophy of liberal nationalism. Liberalism and nationalism are two very different moral and political philosophies. Liberal claims protect individual freedom, advocate open borders, and promote equality of all before the law and consent of the governed. Nationalist philosophy promotes the interests of the state, and advocates devotion to the state, its ideology, culture and ethos. In the context of forced migration, the ideas of these disunited philosophies can be utilised to balance and accommodate the concerns of refugees, states and citizens. For this, I will examine the philosophies of liberalism, nationalism and liberal nationalism, which present an inclusive form of nationalism.